CONTROLE DE PODRIDÃO DE ESCLERÓDIO EM TOMATEIRO COM DIFERENTES FUNGICIDAS. - SANTOS, Ana Luiza Rati do; GRAICHEN, Felipe André Sganzerla; MORI, Micheri; SANTO, Tiago Lima do Espírito (ANAIS DO ENIC, 2017)
-